The Influence of Principal's Academic Supervision, Teacher's Professionalism on the Quality of Education - Mursiani, Mursiani (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The goal of this study was to ascertain how the academic oversight provided by the principal and the professionalism of the faculty affected the educational standards of the public elementary schools in Cengal District, Ogan Komering Ilir Regency. This study uses a quantitative descriptive methodology. A questionnaire tool that the researcher devised was used to gather data. Regression analysis was used to assess all of the research data. Using stratified random sampling, respondents were selected by taking into consideration the 98 instructors who served as research participants from the various strata of the overall population. The study’s findings indicate that: (1) The school principal’s academic oversight has a good and considerable impact on educational quality, increasing it by 30.9%. This implies that the quality of education will increase in direct proportion to the principal’s academic oversight. (2) There is a 20.2% positive and significant correlation between teacher professionalism and academic quality. This suggests that the quality of education will increase in direct proportion to the professionalism of the teachers. (3) The academic oversight of school principals and teacher professionalism have a combined favorable and considerable influence on the quality of public elementary school education by a factor of 36.3%. It suggests that the quality of education will increase in direct proportion to the effectiveness of the principal’s academic oversight and the professionalism of the faculty.